Suppression of Aedes mosquito populations with the boosted sterile insect technique in tropical and Mediterranean urban areas - Jérémy Bouyer; David Almenar Gil; Ignacio Pla Mora; Vicente Dalmau Sorlí; Hamidou Maiga; Wadaka Mamai; Iris Claudel; Ronan Brouazin; Hanano Yamada; Louis-Clément Gouagna; Marie Rossignol; Fabrice Chandre; et al. (Scientific Reports)
Abstract Aedes mosquitoes are the vectors of dengue viruses and other arboviruses, which threaten billions of people all over the world. The boosted sterile insect technique (boosted SIT) is a version of SIT in which irradiated sterile males also transmit a biocide to immature stages. We describe three field trials that were run in 2021: one against Aedes aegypti in La Reunion and two against Aedes albopictus in Spain, each using pyriproxyfen as a biocide. The relative density of adults (compared to their density in control sites: without sterile male release) decreased from 1.00 to 0.09, 95% credible interval [0.06, 0.15] (La Reunion, July) and to 0.02 [0.01, 0.03] and 0.11 [0.08, 0.16] (Spain, July and October). The success rate, corresponding to the proportion of traps with suppression greater than 80%, ranged from 0.43 to 0.71 in La Reunion, from 0.26 to 1.00, and from 0.50 to 0.70 in Spain. In Spain, suppression with boosted SIT was higher than with non-boosted SIT, in 2020 and 2022. This work is in line with the predictions of the model of a better efficacy of boosted SIT compared to SIT, together with partial protection from invasion of treated areas by fertile females, paving the way for larger-scale field trials.